Choroidal structure in subtypes of polypoidal choroidal vasculopathy determined by binarization of optical coherence tomographic images. (10th February 2019) - Liu, Bing; Zhang, Xiongze; Mi, Lan; Peng, Yuting; Wen, Feng
Abstract: Importance: Chorodial structure in subtypes of polypoidal choroidal vasculopathy (PCV). Background: To evaluate choroidal vascularity in the eyes of patients with PCV with and without choroidal vascular hyperpermeability (CVH). Design: A hospital‐based retrospective study. Participants: Fifty‐eight PCV patients (28 with CVH; 30 without CVH) and 30 normal controls were included in this study. Methods: All study subjects underwent spectral‐domain optical coherence tomography with enhanced depth imaging, and the choroidal images were binarized into the luminal area and stromal area. Main Outcome Measures: Choroidal vascularity index (CVI) and subfoveal choroidal thickness (SFCT). Results: Compared to normal controls, patients with PCV showed no obvious difference in SFCT ( P = 0.510), but significantly lower CVI ( P = 0.003). Among PCV patients, the CVI in eyes with CVH was significantly greater than that in those without CVH (65.78 ± 4.70 vs 62.28 ± 3.90; P = 0.002), and a significant difference in SFCT was also found between the two subtypes of PCV (340.8 ± 89.2 vs 250.4 ± 67.7; P < 0.001). Conclusions and Relevance: PCV eyes with CVH have a greater CVI and a thicker SFCT than those without CVH. The significant differences in choroidal vascularity between the two subtypes of PCV may broaden our understanding of the pathogenesis of this disease and contribute to significant improvements in treatment.